2012
DOI: 10.1186/1477-7517-9-39
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cigarette smoking among school adolescents in eastern Ethiopia: a cross-sectional study

Abstract: BackgroundThe World Health Organization (WHO) attributes more than 4 million deaths a year to tobacco, and it is expected that this figure will rise to 10 million deaths a year by 2020. Moreover, it is now a growing public health problem in the developing world.ObjectiveTo assess the prevalence of cigarette use and its determinant factors among high school students in eastern Ethiopia.MethodsA cross-sectional study was conducted using structured self-administered questionnaires among 1,721 school adolescents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
67
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 21 publications
22
67
4
3
Order By: Relevance
“…The current study included a total number of (370) smoking adolescents who participate in this study, their mean age was 16.8 with the most group ages of the participant were (17-19) years, and this finding is similar to Karimy et al, 2013 study, it found that the mean age for participants is 16.49 (12) also Reda et al, 2012 did find the same result and his research stated that the mean age is 16.4 years (13) , in addition to that the most of the participants were living in urban areas and that the same finding result of Amin et al, 2011 found that the urban students were more the half of the participants (14) . Moreover, the dominant marital status of the smoking adolescents was the single status Reda et al, 2012 had mentioned that in his study where the most of his participants were single (13) , that result was expected because of the nature of the Iraqi society and the age of the participants in this period of life it is usually to be single.…”
Section: Part I: Socio-demographic Data Of the Smoking Adolescentssupporting
confidence: 78%
See 1 more Smart Citation
“…The current study included a total number of (370) smoking adolescents who participate in this study, their mean age was 16.8 with the most group ages of the participant were (17-19) years, and this finding is similar to Karimy et al, 2013 study, it found that the mean age for participants is 16.49 (12) also Reda et al, 2012 did find the same result and his research stated that the mean age is 16.4 years (13) , in addition to that the most of the participants were living in urban areas and that the same finding result of Amin et al, 2011 found that the urban students were more the half of the participants (14) . Moreover, the dominant marital status of the smoking adolescents was the single status Reda et al, 2012 had mentioned that in his study where the most of his participants were single (13) , that result was expected because of the nature of the Iraqi society and the age of the participants in this period of life it is usually to be single.…”
Section: Part I: Socio-demographic Data Of the Smoking Adolescentssupporting
confidence: 78%
“…Moreover, the dominant marital status of the smoking adolescents was the single status Reda et al, 2012 had mentioned that in his study where the most of his participants were single (13) , that result was expected because of the nature of the Iraqi society and the age of the participants in this period of life it is usually to be single.…”
Section: Part I: Socio-demographic Data Of the Smoking Adolescentsmentioning
confidence: 99%
“…Um dos principais resultados deste estudo aponta para a relação entre possuir amigos fumantes e o uso regular de cigarros entre os adolescentes. Esses dados concordam com os de outros estudos realizados no Brasil 12,15,16,17 e nos Estados Unidos 14,18,19,20 , entre outros países 21,22,23,24 . Pesquisa que avaliou, qualitativamente, os fatores socioculturais associados à iniciação e cessação do uso do tabaco mostrou que a pressão dos amigos foi um dos mais importantes fatores de influência para a iniciação e uso regular do cigarro 25 .…”
Section: Discussionunclassified
“…Overall prevalence was higher than Çukurova but significantly lower than Sivas, Eskişehir students' smoking prevalence during those years (Metintaş et al, 1998;Saatci, et al, 2004;Demirel et al, 2005). Significant difference between genders have been found in previous studies and mainly attributed to traditional gender roles in Turkish culture which still has influence despite changing social and economic status (Saatci et al, 2004;Erbaydar et al, 2005). In the 2012-2013 educational year there was significant decrease of smoking prevalence; from 26.9% to 18.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, the odds of being smoker were high if a student was male, had smoker mother/ sibling/peer, had low school success, was of low familial income, or lived at places except for dormitories although these correlates of being smoker are not peculiar to Turkish university students. All around the world tobacco consumption studies revealed these associates of smoking (Kabir, 2007;Binu et al, 2010;Cai et al, 2012;Reda et al, 2012;Hussain et al, 2013;Kaleta et al, 2013;Karimy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%